Nutrition of free‐living Neotropical psittacine nestlings and implications for hand‐feeding formulas. Issue 5 (5th July 2022) - Cornejo, Juan; Dierenfeld, Ellen S.; Renton, Katherine; Bailey, Christopher A.; Stahala, Caroline; Cruz‐Nieto, Javier; Brightsmith, Donald J.
Abstract: Psittacidae is one of the most endangered families of birds in the world. Knowledge of their nutrition is important for understanding their survival and productivity in the wild, as well as for their adequate husbandry under human care. Hand‐rearing is a common practice for psittacines, however research on their nutrition is limited. We analysed the predicted metabolisable energy, crude protein, crude fat, minerals and the essential amino acid profiles of the crop contents from free‐living nestlings of scarlet macaws ( Ara macao ) and red‐and‐green macaws ( Ara chloropterus ) from southeastern Peru, Cuban Amazons ( Amazona leucocephala bahamensis ) from the Bahamas, lilac‐crowned Amazons ( Amazona finschi ) from northwestern Mexico and thick‐billed parrots ( Rhynchopsitta pachyrhyncha ) from northern Mexico. The crop content of the different parrot species displayed remarkably similar nutritional profiles, considering their diversity in habitats, geographic ranges and food sources. The crude protein and crude fat concentrations in crop samples were particularly similar for the Ara and Amazona species, while the thick‐billed parrot stood out for its higher crude fat and lower crude protein content. Wider variations were found among the concentrations of sodium (Na) and iron (Fe), proline and tryptophan. Compared with the requirements of 6−12 weeks leghorn chickens, all free‐ranging parrot diets contained lower crude protein, calcium (Ca), potassium (P) and Na concentrations. The hand‐feeding formulas contained lower crude fat, magnesium (Mg), arginine, valine and phenylalanine concentrations, as well as much higher levels of Ca and zinc (Zn), in comparison with parrot crop samples. Our data suggest that a single formulation could be used to hand‐rear Ara and Amazona sp. of 3 weeks of age and older, while a different formulation would likely be more appropriated for Rhynchopsitta sp. Experimental studies should evaluate if increasing the concentration of crude fat, Mg, arginine, valine and phenylalanine enhances psittacine chick growth and health.